(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The phenomenon of suicide represents the existence of social malaise. We come across a situation represented by the operation of a variety of social forces due to which the individual finds that he cannot cope with the tensions and strains, which threaten to engulf him. Under social such circumstances the behavior of a potential suicide may be reflective of this “Cry of help” which, when ignored, may result in a “shout of protest” in the form of indulging in self-immolation.It may happen mainly due to some of the negative life experiences such as death of loved one, divorce, separation or breakup of a relationship, serious loss such as a loss of a job, house, or money, Chronic physical pain, intense emotional pain, loss of hope, (Being victimized such as domestic violence, rape, assault), A loved one being victimized such as child murder, child molestation, kidnapping, murder, rape, assault, Physical abuse, verbal abuse. Sexual abuse, serious legal problems, such as criminal prosecution or incarceration, inability to deal with a perceived "humiliating" situation, inability to deal with a perceived "failure, Alcohol abuse, drug abuse, feeling of not being accepted by family, friends, or society, horrible disappointment, feeling like one has not lived up to his or her high expectations or those of another and low self-esteem. The current paper highlights the facts about suicide and its consequences.